How do BRAFV600E and TERT promoter mutations interact with the ATA and TNM staging systems in thyroid cancer? - Mukhtar, Noha; Alhamoudi, Kheloud; Alswailem, Meshael; Alhindi, Hindi; Murugan, Avaniyapuram Kannan; Alghamdi, Balgees; Alzahrani, Ali S. (Frontiers in Endocrinology, 2023)
The American Thyroid Association risk stratification (ATA) and the American Joint Committee on Cancer Tumor Node Metastases (TNM) predict recurrence and mortality of differentiated thyroid cancer (DTC). BRAF V600E and TERT promoter mutations have been shown to correlate with the histopathological features and outcome of DTC. Our objectives were to study the correlation of these molecular markers with these clinicopathological-staging systems.We studied 296 unselected patients, 214 females and 82 males with a median age of 36 years . BRAF V600E and TERT promoter mutations were tested by PCR-based Sanger sequencing. Data were extracted from medical records and analysed using Chi-Square and Fisher Exact test and Kaplan Meier analysis.Results: Of 296 patients tested, 137 (46.3%) had BRAF V600E -positive tumors and 72 (24.3%) were positive for TERT promoter mutations. The BRAF V600E mutation did not correlate with the ATA and TNM staging, being non-significantly different in various stages of these systems and did not predict the development of persistent disease (PD) (P 0.12). Unlike BRAF V600E , TERT promoter mutations were more frequent in the ATA high-risk than in intermediate-or low-risk tumors (P 0.006) and in TNM stages III and IV than lower stages (P <0.0001). TERT promoter mutations also predicted the outcome, being present in 37.2% of patients with PD compared to only 15.4% in those without evidence of disease (P <0.0001).The same pattern was also seen when BRAF V600E and TERT promoter mutations were combined.Conclusions: TERT promoter mutations alone or in combination with BRAF V600E mutation, but not BRAF V600E mutation alone, correlated well with the ATA and TNM staging and predicted development of PD, especially in higher stages of these systems.